A Study on Localization in Wireless Sensor Networks using Frequency Diversity for Mitigating Multipath Effects - Lazaro, A.; Girbau, D.; Moravek, P.; Villarino, R. (Elektronika ir Elektrotechnika, 2013)
Self-localization capability is for many ad-hoc network deployments an essential feature. Unfortunately, the radio environment introduces a several phenomenons which negatively influence the accuracy of the localization. In this paper we investigate the effect of multipath propagation in outdoor environment on accuracy of localization and propose a method using frequency diversity for RSS measurement in order to mitigate the fading caused by multipath propagation. To that end, a localization algorithm based on least square minimization of measured distance and weighted centroid algorithm are used to verify the frequency diversity concept. The results of simulations and measurements are presented also with the relation to an antenna height. DOI: http://dx.doi.org/10.5755/j01.eee.19.3.3701